Attitudes Toward HPV Vaccination in Sweden: A Survey Study - Maria Wemrell; Maria Wemrell; Lena Gunnarsson (Frontiers Media S.A., 2022)
BackgroundWhile HPV vaccination uptake in Sweden is quite high, at around 80%, vaccine hesitancy remains an issue in countries throughout Europe. The latter can be related to a contemporary context of increased contestation of expert knowledge and of a large share of information on health-related issues including vaccination today being sought via the internet. Still, there is a paucity of recent research on attitudes toward the HPV vaccine in a larger sample of the population in Sweden. This survey study assesses such attitudes and any correlations between vaccine hesitancy and sociodemographic characteristics, trust in healthcare and other societal institutions, and evaluation of the reliability of different sources of information.MethodsThe validated survey questionnaire was distributed to adult women in Sweden (n = 2,000), via a nationally representative web panel. The response rate was 37%. Aside from descriptive statistics, associations between vaccine hesitancy and sociodemographic and other variables were computed using logistic regressions and expressed as odds ratios (ORs) with 95% confidence intervals (95% CIs).ResultsOur results show a positive attitude toward HPV vaccination overall. Still, some degree of HPV vaccine hesitancy was indicated by 33.8% of the respondents, and more pronounced hesitancy by 7.6%. Regarding vaccination in general, a very positive attitude was indicated by 55%. HPV vaccine hesitancy was associated with low education and low income and strongly associated with a lack of confidence in healthcare and other societal institutions. It was also correlated with a self-assessed lack of access to, and ability to assess the origin, quality and reliability of, information about the HPV vaccine.ConclusionEfforts to provide transparent information about HPV vaccination should be combined with healthcare providers being open to discuss vaccine concerns with patients and avoiding practices that do not promote trust.